CEDERA PADA PERMAINAN BOLABASKET - Ani Hastuti, Tri (Jurnal Pendidikan Jasmani Indonesia, 2006)
Basketball has an attractive and dynamic pattern on defending and attacking thus requiredgood stamina, and if the game is tense enough, it can develop stress. Stress effecting themental side and the organ functions.The technicality side of basketball are rich with agility, adroit, and tricky movement (eye,hands, and foot). This make basketball interesting but also it is the source of the injuryproblem.The grounds of injury in basketball can be trace into two cause; external and internal. Inexternal violence, the cause of an injury came from the outside party. In the internal violence,the cause came from the inside because the overuse of the body and causing an injury.There are three classifications of injury in basketball, light injury, medium injury and heavyinjury. It can be bruise, scratch, muscle or ligament injury (strain and sprain), dislocation,broken bone, bleeding, and faint.Keyword: injury, basketball.